Surface oxidation of porous ZrB2-SiC ceramic composites by continuous-wave ytterbium fibre laser - Dayang Salyani, Abang Mahmod; Glandut, Nicolas; Amir Azam, Khan; Labbe, Jean Claude (Elsevier, 2015)
Surface treatment of ceramic substrates by a laser beam can allow to incorporate interesting properties to these ceramics. In the present work, surface oxidation of ca. 30% porous ZrB2-SiC ceramic composites by using an ytterbium fibre laser was conducted. Oxidation of ceramic substrates through this process under ambient conditions has certain advantages compared to the classical oxidation method. A particular spiral laser pattern was created in order to produce an oxidized structure on ZrB2-SiC porous substrates. The laser parameters were as follows i.e., laser power of 50, 60 and 70 W, a beam diameter of 1.25 mm, velocity of 2 mm/s, acceleration and deceleration of 1 mm/s2. The microstructural and morphological changes in the laser-treated region was examined using scanning electron microscopy, energy dispersive X-ray spectroscopy, and X-ray diffraction. At laser power of 70 W, the sample exhibits uniform oxidation. It revealed that the very porous bulk beneath remained unaffected and unoxidized because this laser-formed oxide scale protects the substrate from oxidation. The presence of oxidized and unaffected regions indicated a high degree of heat localization. The dense glassy SiO2-rich layer prevents the inward oxygen diffusion into the inner bulk hence enhances the oxidation resistance.